Properties and Applications of Metal (M) dodecahydro-closo-dodecaborates (Mn=1,2B12H12) and Their Implications for Reversible Hydrogen Storage in the Borohydrides - Aiden Grahame; Kondo-François Aguey-Zinsou (Inorganics, 2018)
Hydrogen has long been proposed as a versatile energy carrier that could facilitate a sustainable energy future. For an energy economy centred around hydrogen to function, a storage method is required that is optimised for both portable and stationary applications and is compatible with existing hydrogen technologies. Storage by chemisorption in borohydride species emerges as a promising option because of the advantages of solid-state storage and the unmatched hydrogen energy densities that borohydrides attain. One of the most nuanced challenges limiting the feasibility of borohydride hydrogen storage is the irreversibility of their hydrogen storage reactions. This irreversibility has been partially attributed to the formation of stable dodecahydro-closo-dodecaborates (Mn=1,2B12H12) during the desorption of hydrogen. These dodecaborates have an interesting set of properties that are problematic in the context of borohydride decomposition but suggest a variety of useful applications when considered independently. In this review, dodecaborates are explored within the borohydride thermolysis system and beyond to present a holistic discussion of the most important roles of the dodecaborates in modern chemistry.